Reason and Writing. Miracle, Revelation and Interpretation of the Bible in the Philosophy of Christian Wolff - Banaszkiewicz, Artur (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
This analytical and reconstructive paper discusses the issues of a miracle and of revelation in Christian Wolff’s rationalistic philosophy. The article comprises three major parts: in the first one I introduce Wolff’s conception of nature, followed by the conception of the supernatural and the outline of Wolff’s conception of a miracle. In the second one I talk about the issue of the rationality of revelation based on seven signs of its genuineness put forward by Wolff. In the third one I discuss the principles of understanding and interpreting text, especially Scripture. Finally, I evaluate Wolff’s apologetic strategy and point out that his means of defending both revelation and religion founded in it, can be very well used against them.